2021
DOI: 10.1016/j.heliyon.2021.e06933
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of nursing process during patient care in Ethiopia: A systematic review and meta-analysis

Abstract: Background: Nursing process (NP) is a standard method of ensuring individualized holistic care through systematic assessment, diagnosis, planning, intervention and evaluation of patients. Its standard implementation is mandatory to meet the health target of "ensuring universal quality health-care services" in the sustainable development goals (SDG) launched by World Health Organization (WHO) in 2015. Being a member state of WHO, Ethiopia endorsed the SDG agenda. Therefore, determining the recent pooled estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…25 Moreover, a high number of SR might lead to research waste, as the publication of overlapping SR and MA is becoming evident. 26, 27 For example, we found 28 duplicates on various topics: two on mother-to-child transmission of HIV 28, 29 , two on HIV/AIDS treatment failure 30, 31 , three on nursing process 32-34 , three on antenatal depression 35-37 , three on postnatal depression 38-40 , three on breastfeeding 41-43 , three on immunization coverage 44-46 , three on low birth weight 47-49 , two on tuberculosis treatment non-adherence 50, 51 , two on maternal-near miss 52, 53 and two on antiepleptive medication non-adherence. 54, 55 To minimize research waste, authors must register their protocol, thoroughly search protocol registration cites and communicate each other whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, a high number of SR might lead to research waste, as the publication of overlapping SR and MA is becoming evident. 26, 27 For example, we found 28 duplicates on various topics: two on mother-to-child transmission of HIV 28, 29 , two on HIV/AIDS treatment failure 30, 31 , three on nursing process 32-34 , three on antenatal depression 35-37 , three on postnatal depression 38-40 , three on breastfeeding 41-43 , three on immunization coverage 44-46 , three on low birth weight 47-49 , two on tuberculosis treatment non-adherence 50, 51 , two on maternal-near miss 52, 53 and two on antiepleptive medication non-adherence. 54, 55 To minimize research waste, authors must register their protocol, thoroughly search protocol registration cites and communicate each other whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Nurses should be educated about care strategies, and they know the principles of care scientifically. [ 13 ] The present study is based on the findings of nurses’ reports in hospitals of Iran. It shows that nurses were successful in performing many aspects of the excretion, absorption, and dressing processes and showed appropriate preparation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that paying attention to influential factors such as stressful environment, lack of facilities, and access to education can be effective in improving care and nursing processes. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Bayih et al . [ 8 ] showed that that only half of the nurses performed the nursing processes completely during the patient care. They stated that paying attention to influential factors such as stressful environment, the lack of facilities, and access to education can be effective in improving care and nursing processes.…”
Section: Discussionmentioning
confidence: 99%
“…By empowering nurses, effective steps can be taken to address nursing challenges. [ 7 8 ] So far, many studies have been conducted in relation to the readiness of nurses, but despite the increasing challenges of nursing and the need of patient health, attention and evaluation of nursing care are important issues. Also, the identification of these deficiencies in different wards of hospitals can be performed with the aim of comparing the readiness of nurses in the field of evaluation of clinical nursing care in different wards of hospitals.…”
Section: Introductionmentioning
confidence: 99%